2020
DOI: 10.3390/foods9121895
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Blue Light versus Pathogenic Bacteria: Mechanism, Application in the Food Industry, Hurdle Technologies and Potential Resistance

Abstract: Blue light primarily exhibits antimicrobial activity through the activation of endogenous photosensitizers, which leads to the formation of reactive oxygen species that attack components of bacterial cells. Current data show that blue light is innocuous on the skin, but may inflict photo-damage to the eyes. Laboratory measurements indicate that antimicrobial blue light has minimal effects on the sensorial and nutritional properties of foods, although future research using human panels is required to ascertain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 259 publications
(174 reference statements)
1
30
0
1
Order By: Relevance
“…The XTT activity of strain ES191 and AGRFS2961 showed that the whole population could sustain comparable metabolic rates as the control cells during the light treatment ( p > 0.05) ( Figure 1 e,f), suggesting that the light treated populations were still metabolically active ( p < 0.05). The DCFH–DA assay demonstrated that ROS production increased after 1 h of light treatment (where the cell loss became significant) ( Figure 1 and Figure 3 ), supporting the finding that light induced ROS against many different bacteria was time-dependent [ 9 , 10 ]. After 2 h, blue-LED treated samples had a reduced number of viable cells, which led to the decrease of overall ROS levels in the whole population.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The XTT activity of strain ES191 and AGRFS2961 showed that the whole population could sustain comparable metabolic rates as the control cells during the light treatment ( p > 0.05) ( Figure 1 e,f), suggesting that the light treated populations were still metabolically active ( p < 0.05). The DCFH–DA assay demonstrated that ROS production increased after 1 h of light treatment (where the cell loss became significant) ( Figure 1 and Figure 3 ), supporting the finding that light induced ROS against many different bacteria was time-dependent [ 9 , 10 ]. After 2 h, blue-LED treated samples had a reduced number of viable cells, which led to the decrease of overall ROS levels in the whole population.…”
Section: Discussionsupporting
confidence: 72%
“…However, it is still a UV-containing application. Visible light (especially blue light wavelengths from 405 to 465 nm) has been shown to have antimicrobial properties and inactivates microbes via photodynamic inactivation, where cellular molecules known as photosensitizers produce reactive oxygen species which react with cellular constituents such as lipids, proteins, and DNA to bring about a cytotoxic effect [ 9 ]. Our previous study showed that blue-LED at 405 nm caused a significant reduction (to extinction) in the levels of Escherichia coli (Shiga-toxin producing E. coli ) in vitro [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Guffey and Wilborn (2006) [62] studied the effect of radiation with a wavelength of 405 nm and 470 nm on the species Staphylococcus aureus, Pseudomonas aeruginosa, and Propionibacterium acnes; they noted that both types of lighting showed bactericidal effect on P. aeruginosa and S. aureus, but not on Propionibacterium acnes. Different scientists studied the effect of blue light (470 nm) on several strains of methicillin-resistant Staphylococcus aureus and the results showed that the number of colony-forming units (CFUs) of the samples exposed to light radiation of 470 nm was smaller than in the case of non-irradiated ones [63,64]. Maclean et al (2009) [52] studied the effect of light with a wavelength of 405 nm on several microbial strains responsible for nosocomial infections and observed that both Gram-positive and Gram-negative strains were inactivated after exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Photosensitization treatment can be used as an alternative to curb fungal growth on peanuts. The treatment combines a photosensitizer and light at the appropriate wavelength, in the presence of oxygen, to produce a cytotoxic effect towards microorganisms [15,16]. The increasing popularity of the photosensitization treatment is due to its cytotoxic effect towards a wide range of microorganisms, including Gram-negative and Gram-positive bacteria, fungi, parasites and viruses, as well as ensuring the non-emergence of resistant strains [17].…”
Section: Introductionmentioning
confidence: 99%